FUNGSI DAN PERAN BPOM DALAM PERLINDUNGAN KONSUMEN TERHADAP MAKANAN YANG MENGANDUNG BAHAN BERBAHAYA DI KOTA SEMARANG - Atin Carolina Parei; Fitika Andraini (Jurnal Ilmiah Dinamika Hukum, 2018)
The issue of legal protection for consumers is one that is championed in order to provide protection for the community as consumers. BPOM Semarang City has the duty to provide services for the community to supervise the circulating products to ensure their safety, however, there are still products that contain hazardous substances in circulation. Therefore this thesis is entitled "The Function and Role of BPOM in Consumer Protection Against Foods Containing Hazardous Ingredients in Semarang City". The problem under study is to find out how the function and role of BPOM in dealing with food containing hazardous ingredients, what efforts have been made by BPOM on foods containing hazardous ingredients and the rights obtained by consumers in order to be safer against substances that contain hazardous ingredients. The research method used is the type of normative juridical legal research. Specific research is descriptive analysis of primary and secondary data sources. Data collection methods used are interviews and literature study with research locations at BPOM Semarang City. Based on the research obtained shows that the position of consumers is weak compared to producers, so consumers need the existence of UUPK and POM agencies as supervisors on the feasibility and safety of drugs and food to avoid losses suffered by consumers considering that there are still dangerous substances in the circulating products. The role of the government needs to be maximized in controlling, supervising and coaching and counseling to consumers and businesses.